1984
DOI: 10.1192/bjp.145.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Hospital Admissions in Bristol. II. Social and Clinical Aspects of Compulsory Admission

Abstract: Three groups of patients admitted compulsorily from populations with markedly different rates of compulsory psychiatric admissions were compared on a range of social and clinical data. Whilst West Indian and white patients from inner city areas differed in many respects, they were both more likely than other patients to be referred to the psychiatric services through police agencies, with little GP involvement and were often admitted from public places following disturbed behaviour. However, levels of violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 13 publications
3
29
1
Order By: Relevance
“…In contrast, Tunnicliffe, Harrison, and Standen (1992) investigated aspects of community psychiatric care in an Afro-Caribbean community and found that ethnicity was not a major factor affecting compliance with depot medication. Most studies show little or no association between socio-demographic factors and compliance (Buchanan, 1992;Harrison, Ineichen, Smith, & Morgan, 1984;Owen, Fischer, Booth, & Cuffel, 1996;Razali & Yahya, 1995;Sellwood & Tarrier, 1994).…”
Section: Patient-related Factorsmentioning
confidence: 96%
“…In contrast, Tunnicliffe, Harrison, and Standen (1992) investigated aspects of community psychiatric care in an Afro-Caribbean community and found that ethnicity was not a major factor affecting compliance with depot medication. Most studies show little or no association between socio-demographic factors and compliance (Buchanan, 1992;Harrison, Ineichen, Smith, & Morgan, 1984;Owen, Fischer, Booth, & Cuffel, 1996;Razali & Yahya, 1995;Sellwood & Tarrier, 1994).…”
Section: Patient-related Factorsmentioning
confidence: 96%
“…The statistical techniques used here can now give numerical values to the associations between social deprivation within inner-city areas and rates of treated mental disorder, associations which have previously been documented descriptively in Chicago, Bristol, Nottingham, and Mannheim (Fans & Dunham, 1939;Hare, 1956;Harrison et al, 1984;Ineichen et al, 1984;Giggs & Cooper, 1987;Maylath et a!, 1989). There is supportive evidence for these quantitative associations from three other sources.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of hostility among black patients to the psychiatric services, which some see as racist and coercive (Cope, 1989) and there is also evidence of hostility to other parts of the health and welfare services (Donovan, 1986). There have been suggestions that black patients are perceived as hostile and aggressive by health workers but this received only qualified support from the literature (Bolton, 1984;Harrison et al 1984;Dunn & Fahy, 1990;Soothill et al 1990, Pipe et al 1991). …”
Section: Schizophrenia In British Afro-caribbeansmentioning
confidence: 93%
“…Black people have been shown repeatedly to be more likely to be admitted compulsorily, under a section of the Mental Health Act (Ineichen, 1986;Cope, 1989;Pipe et al 1991;Owens et al 1991). Police are more likely to be involved, and GPs less likely, when the compulsory admission concerns an Afro-Caribbean patient (Harrison et al 1984;Owens al. 1991).…”
Section: Schizophrenia In British Afro-caribbeansmentioning
confidence: 97%